Le imprese di cartografia aerofotogrammetrica in Italia - Selvini, Attilio (GEOmedia, 2013)
When it was born the aerial photogrammetric technique for cartographic purposes, at the beginning of the twenties of the twentieth century, in European countries where the new discipline had spread (Italy, France, Germany, Switzerland, Austria, Great Britain) were built businesses of survey and cartographic representation, next to the state agencies obviously interested in new techniques (cadastre, national geographic institutes or military). We recall here the vicissitudes of our country, because they are quite different from those developed across the Alps.